A review of Cuvier’s beaked whale strandings in the Mediterranean Sea - Podesta , Michela; D'Amico, Angela; Pavan, Gianni; Drougas , Aimilia; Komnenou, Anastasia; Portunato , Nicola (J. Cetacean Res. Manage., 2023)
Cuvier’s beaked whale (Ziphius cavirostris) is the only species of beaked whale commonly found in the Mediterranean Sea, a deep, semienclosed basin. Beaked whales are generally an offshore family often found in association with the canyons and steep escarpments common to the area. Much of the current knowledge of this species has been derived from strandings data. Historically, strandings data for the Mediterranean Sea has been collected by individual researchers and more recently, over the last two decades, by national strandings networks. We reviewed strandings data collected by strandings networks from Italy, Greece, Spain and France. Additionally, we compiled strandings information gleaned from the literature, personal communications, regional newspapers and the world wide web from countries that border the Mediterranean Sea. While this review is certainly not exhaustive, it has allowed the creation of an extensive geo-referenced basin wide database using a geographic information system (GIS) of over 300 stranding events. The acquired data permit documentation of the number of mass stranding events, allow general observations about distribution and chronology of stranding events dating back to 1803 and enables evaluation of strandings based on several different criteria. The first recorded mass stranding event was in 1963 off Genova, Italy. Analysis shows that specific geographic stranding areas can be identified, even though the level of effort undertaken in the different countries may vary.